The Right of ‘Manifestacion’ in the Kingdom of Aragon: Origins and Legal Heritage - David Manuel Rodríguez Ferro (Journal on European History of Law, 2023)
This article aims to expose a characteristic procedural figure of the Kingdom of Aragón (Spain), a peculiarity within the strict medieval legal codes whose foundation was extended to other territories almost a century after its creation, with close links to Habeas Corpus Act. Its use produced controversial situations at certain times that led to reprisals and legal and political reforms in Aragon and in the judicial institution of ‘Justicia de Aragón’. This work aims to make known the peculiarities of this procedural figure, as well as those of the institution of ‘Justicia’, one of the oldest legal institutions in force today around the world, also mentioning to the nuances between ‘Derecho de Manifestación’ and the Habeas Corpus Act. A deductive and descriptive method is employed in order to show a general overview prior to discuss each particular topic.